2022
DOI: 10.1249/mss.0000000000003062
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Running-Induced Fatigue on Tibial Acceleration and the Role of Lower Limb Muscle Strength, Power, and Endurance

Abstract: Background: Highimpact loads have been linked with running injuries. Fatigue has been proposed to increase impact loads, but this relationship has not been rigorously examined, including the associated role of muscle strength, power, and endurance. Purpose: This study aimed to investigate the effect of fatigue on impact loading in runners and the role of muscle function in mediating changes in impact loading with fatigue. Methods: Twenty-eight trained endurance runners performed a fixed-intensity time to exhau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
(110 reference statements)
1
1
0
Order By: Relevance
“…While the reasons for this increase are not fully understood, the authors speculate that this was also linked to the onset of fatigue which subsequently produced increased movement of the tibia. This aligns with previous research that has shown that peak tibial acceleration increased over the duration of a fatiguing run 10 . Despite the obvious differences in mechanical loading, specifically the axial loads experienced when running on dryland compared to DWR, the relationship between tibia acceleration in the two conflicting settings is an area for future investigation.…”
Section: Discussionsupporting
confidence: 92%
“…While the reasons for this increase are not fully understood, the authors speculate that this was also linked to the onset of fatigue which subsequently produced increased movement of the tibia. This aligns with previous research that has shown that peak tibial acceleration increased over the duration of a fatiguing run 10 . Despite the obvious differences in mechanical loading, specifically the axial loads experienced when running on dryland compared to DWR, the relationship between tibia acceleration in the two conflicting settings is an area for future investigation.…”
Section: Discussionsupporting
confidence: 92%
“…However, accelerometer data are suggested to provide more individualized information. It was already shown that tibial acceleration is modified by running speed [ 18 ] and changed with increasing duration during running with constant speed [ 19 ]. Faster running speeds were associated with increased tibial acceleration, irrespective of running surface, footwear, running experience, or whether the velocity was fixed or self-selected [ 18 ].…”
Section: Introductionmentioning
confidence: 99%